MENAFSIR AYAT SABAR SEBAGAI BASIS TERAPI KESEHATAN MENTAL PASCA PANDEMI COVID-19 (Jurnal An-Nufus, 2023)
This article discusses the relation between the conception of patience and the issue of mental health in several verses of patience (QS. 2:45, QS. 2:153, and QS.:3) which are described in two treasures of interpretation: Tafsir At-Thabari and Tafsir Ar-Razi. The purpose of this research is to investigate the doctrine and teachings of patience as a knowledge base in supporting mental health theories spiritually, especially in the context of the Covid-19 pandemic. The method of investigation and discussion in research is more of a qualitative approach with the object of research being the Divine Word. A number of findings in this research review, among others: the unfolding of the doctrine and conception of patience holistically (exoteric and esoteric) as well as the foundation cum formulation of patient therapy in Islamic mental health discourses.